Acondicionamiento de una cámara bioclimática para el crecimiento de insectos - Acurio Maigua, Leyla Monserrath (2022)
This degree project is mainly based on a temperature control from 0 to 30°C to develop a bioclimatic chamber by means of an automated control system for the growth of insects, generating a controlled environment where the process of hot air entering the chamber is manifested, generating an optimal environment for the survival of insects. In this way, important data will be obtained from the storage device to carry out the risk analysis of the incidence of the increase of insects and pests in different parts of the country. The process consists of regulating the temperature when the bioclimatic chamber is turned on and off, through the design of a system composed of a control unit capable of storing and visualizing the most important variables of the bioclimatic chamber for a safe operation during the use and maintenance of the chamber. For this purpose, an HMI (Human Machine Interface) system was used to visualize historical data and determine the behavior of the temperature in a range of time, in the same way the interaction of the operators with the equipment is made to make the temperature changes in an easier way using the screen that is controlled by a programming made in a Microcontroller, helping to manipulate and visualize in a better way the working speed of the equipment and the output values, through the design of the system adding a datalogger that stores the temperature information to download and analyze the variables of the bioclimatic chamber. The results obtained allow verifying that the bioclimatic chamber helps to reduce the insect rearing time in a period of 15 to 7 days, improving the collection of experimental data.